Cross talk between human regulatory T cells and antigen‐presenting cells: Lessons for clinical applications. Issue 1 (23rd December 2020) - Wardell, Christine M; MacDonald, Katherine N; Levings, Megan K; Cook, Laura
Abstract: Regulatory T cells (Tregs) have a critical role in maintaining self‐tolerance and immune homeostasis. There is much interest in using Tregs as a cell therapy to re‐establish tolerance in conditions such as inflammatory bowel disease and type 1 diabetes, with many ongoing clinical studies testing the safety and efficacy of this approach. Manufacturing of Tregs for therapy typically involves ex vivo expansion to obtain sufficient cell numbers for infusion and comes with the risk of altering the activity of key biological processes. However, this process also offers an opportunity to tailor Treg function to maximize in vivo activity. In this review, we focus on the roles of antigen‐presenting cells (APCs) in the generation and function of Tregs in humans. In addition to stimulating the development of Tregs, APCs activate Tregs and provide signals that induce specialized functional and homing marker expression. Cross talk between Tregs and APCs is a critical, often under‐appreciated, aspect of Treg biology, with APCs mediating the key properties of infectious tolerance and bystander suppression. Understanding the biology of human Treg‐APC interactions will reveal new ways to optimize Treg‐based therapeutic approaches. Abstract : Human regulatory T cell (Treg) induction, activation, suppression, and homing capacities are orchestrated by antigen‐presenting cells (APCs). APCs and Tregs modulate each other's functions via the release of soluble mediators, co‐stimulatory molecule ligation, and immune synapse formation. Understanding the Treg‐APC relationship is critical to guiding clinical Treg therapy improvement.